2011
DOI: 10.1007/s11274-011-0764-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel enzymatic production of trehalose from sucrose using amylosucrase and maltooligosyltrehalose synthase-trehalohydrolase

Abstract: Trehalose (a-D-glucopyranosyl a-D-glucopyranoside) is an important non-reducing disaccharide used in the food industry due to its mild sweetness (45% that of sucrose), low cariogenicity, high glass transition temperature, low hygroscopicity, and protein protection properties. In this study, we accomplished the production of trehalose from sucrose as a sole substrate using a novel dual-enzyme system, in which amylosucrase (ASase) and maltooligosyltrehalose synthase-trehalohydrolase (MTSH) fusion enzyme were emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Trehalose synthases are retaining GTs that catalyze the formation of trehalose, by transferring a glucose from NDP-glucose to another glucose residue. The resulting product is a non-reducing disaccharide that can be used either as a food additive because it has lower sweetness than sucrose, a moderate glycemic index and low cariogenicity, or can serve as a stabilizer in cosmetics and pharmaceuticals due to its high heat and pH resistance, high glass transition temperature, high water retention capacity and protective effect on proteins [160][161][162].…”
Section: Trehalose Synthasesmentioning
confidence: 99%
“…Trehalose synthases are retaining GTs that catalyze the formation of trehalose, by transferring a glucose from NDP-glucose to another glucose residue. The resulting product is a non-reducing disaccharide that can be used either as a food additive because it has lower sweetness than sucrose, a moderate glycemic index and low cariogenicity, or can serve as a stabilizer in cosmetics and pharmaceuticals due to its high heat and pH resistance, high glass transition temperature, high water retention capacity and protective effect on proteins [160][161][162].…”
Section: Trehalose Synthasesmentioning
confidence: 99%
“…Then, maltooligosyltrehalose trehalohydrolase (MTHase) cleaves the -1,4-glucosidic linkage next to the -1,1linkage of trehalosyl-oligosaccharide to produce trehalose and oligosaccharide with lower molecular mass (Kato, 1999). Recently, Kim et al (2011) reported two steps enzymatic production of trehalose from sucrose using amylosucrose from D. geothermalis and maltooligosyltrehalose synthase from Bacillus helvolum. The third pathway, catalyzed by trehalose glycosyltransferring synthase (TreT), involves the conversion of nucleoside diphosphate glucose and glucose, instead of glucose-6phosphate, into trehalose (Ryu et al, 2005;Empadinhas and da Costa, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Among several synthetic strategies studied for the synthesis of trehalose, the biocatalytic one starting from sucrose has aroused considerable interest [60]. The biocatalysts involved in this process are amylosucrase (ASase), maltooligosyl trehalose synthase (MTS) and maltooligosyltrehalose trealohydrolase (MTH).…”
Section: Sucrose To Trehalose Conversionmentioning
confidence: 99%